2014
DOI: 10.3389/fpsyg.2014.00431
|View full text |Cite
|
Sign up to set email alerts
|

Music evokes vicarious emotions in listeners

Abstract: Why do we listen to sad music? We seek to answer this question using a psychological approach. It is possible to distinguish perceived emotions from those that are experienced. Therefore, we hypothesized that, although sad music is perceived as sad, listeners actually feel (experience) pleasant emotions concurrent with sadness. This hypothesis was supported, which led us to question whether sadness in the context of art is truly an unpleasant emotion. While experiencing sadness may be unpleasant, it may also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
0
16
0
4
Order By: Relevance
“…In another study, Tamir and Ford (2009) suggested that some individuals may be willing to experience negative affect as it may prove useful to attain instrumental gain. Additionally, Kawakami et al (2014) found that listening to sad music can be perceived as sad but can evoke positive emotional responses. They suggest that if a negative emotion does not constitute any real threat to the individual, then it generates a positive reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Tamir and Ford (2009) suggested that some individuals may be willing to experience negative affect as it may prove useful to attain instrumental gain. Additionally, Kawakami et al (2014) found that listening to sad music can be perceived as sad but can evoke positive emotional responses. They suggest that if a negative emotion does not constitute any real threat to the individual, then it generates a positive reaction.…”
Section: Discussionmentioning
confidence: 99%
“…kapsayıcı yönü, disiplinlerarası birçok alan ile ilişkisel bir görünüme sahip olmasını hem gerekli kılmış, hem de daha belirgin bir hale getirmiştir. Dolayısıyla son zamanlarda müzik, duygu ve duygudurum üçgeninde yapılan araştırmalar ve analizler incelendiğinde, bu konularda kayda değer bir artışın görülmesi, müzik, duygu ve duygudurumu tanımanın ayrıntılı bir konu haline geldiğini göstermektedir (Baydağ, 2018;Eden, 2016;Gültepe, 2014;Kaufmann & Vosburg, 2002;Kawakami, Furukawa, & Okanoya, 2014;Kim, Schmidt, & Emelle 2010;Markov & Matsu, 2014;Öğüt, 2014;Plewa & Kostek, 2015;Van der Zwaag et al, 2012;Zentner, Grandjean & Scherer, 2008). Müzik ve duygudurum arasındaki ilişki, disiplinlerarası birçok çalışma alanının etkileşim halinde olmasına zemin hazırlamıştır (Juslin & Zentner, 2002).…”
Section: Faydacı Durumsallık Kuramıunclassified
“…Keywords: Emotion, Mood, Human voice, Music psychology Yükseköğretim ve Bilim Dergisi/Journal of Higher Education and Science bir çalışma, müzik eğitimi almış bireylerin hoş olmayan müzikleri (minör ton ya da uyumsuz aralıklar) dinlediklerinde, müzikten hoşnut kaldıkları sonucunu ortaya çıkarmıştır (Kawakami, Furukawa, Katahira, Kamiyama, & Okanoya, 2013). Dolayısıyla hissedilen duyguyu algılanan duygudan ayırt etmek gerekmektedir (Gabrielsson, 2002;Kawakami et al, 2014).…”
Section: Introductionunclassified
“…Thus, the emotion produced by musical stimulation, as could be prosody in the previous model, may influence the stimuli perception of stimuli, presented in other sensory modalities, through a top-down process (Sekuler et al, 1997 ; Jolij and Meurs, 2011 ; Wong and Gauthier, 2012 ). Different musical genres can also modulate arousal and others psychophysiological parameters eliciting different emotions (Schellenberg, 2005 ; Caldwell and Riby, 2007 ; Sammler et al, 2007 ; Fritz et al, 2009 ; Ladinig and Schellenberg, 2012 ; Schellenberg and Mankarious, 2012 ; Kawakami et al, 2014 ; Bhatti et al, 2016 ). For example, Baumgartner and colleagues investigated the psychophysiological effect of the interaction between emotional visual images, music, and a crossmodal presentation (music and images; Baumgartner et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…The N1 component was distributed over the frontal regions, suggesting the involvement of top–down psychophysiological mechanisms (Zanto et al, 2011 ; Gilbert and Li, 2013 ). Moreover, the perception of music is affected by the listener's emotional and cognitive state (Kawakami et al, 2013 , 2014 ). Many studies have highlighted differences between the cognitive processing and cortical responses of musicians and non-musicians (Pantev et al, 1998 ; Brattico et al, 2010 ; Müller et al, 2010 ; Pallesen et al, 2010 ; Herholz and Zatorre, 2012 ; Proverbio et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%